Kajian Hazard Analysis Critical Control Point (HACCP) Pada Tahap Pasteurisasi II Susu ISAM Di PT Industri Susu Alam Murni - Shafiyyah Dzakirah Hasna; Irfan Ardiansah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2023)
Milk is a food source that contains essential nutrients for the human body so it cannot be reduced or added to its natural content. Milk can be processed into several products, namely food, beverages, cheese, butter, yogurt, and so on. Therefore, the milk processing industry has considerable opportunities in the industrial sector because milk is one of the many food ingredients that are used as basic needs by people in all walks of life. In processing, the HACCP system is used as a tool that can maintain food safety and improve product quality. One of the stages of the milk processing process that has the potential to be dangerous is the pasteurization process. The studies of HACCP is needed to identify hazards using the 7 HACCP principles that have been issued by the Indonesian National Standard. The conclusion obtained from the study is that the pasteurization process 2 is designated as CCP because it is a sterilization process that has the potential to be dangerous, so supervision and control must be carried out. The verification process has an important role in that it can demonstrate the effectiveness of the implementation of HACCP. With HACCP, the products produced are expected to be of high quality and food safety is guaranteed